St Kilda: the pre-Improvement clachan - Fleming, Andrew (Proceedings of the Society of Antiquaries of Scotland, 2004)
Archaeological studies of Hirta, the main island of the St Kilda archipelago to the west of the Western Isles of Scotland, have debated the location and character of the settlement demolished during the Improvement phase of the 1830s. This paper argues that archaeological evidence for the clachan is recoverable, and that it is in very good agreement with the drawings made by Acland and Atkinson in the early 19th century.